DETERMINANTS OF COMMUNITY INTEREST IN TRANSITING IN SHARIA BANKING - Bayu Tri Cahya; Eskasari Putri; Salma Badriyah (Jurnal Ekonomi dan Manajemen, 2021)
The financial industry has an important role in a country's economy, the industry referred to in this case is the Islamic banking industry. This study aims to determine the determinants of interest in transactions in Islamic banking through aspects of attitude, subjective norms, perceived behavioral control and religiosity. With BRI Syariah Purwodadi customer subjects using the questionnaire method. The results of this study indicate that the variables that show a significant positive influence on interest are the variables of attitude, subjective norms and religiosity. While the variables that do not have a significant influence are perceived behavior control variables.